Sustainable leadership as a strategy of change in the Venezuelan education system (Docentes 2.0 Journal, 2020)
The definition of sustainable leadership is determined by the reasonable improvement that preserves and develops deep learning for everything that evolves and endures, so that a real benefit can be generated for the Venezuelan educational system in the future; This is how it can be the starting point that guides the configuration of the sustainability of leadership in education as a moral concept and practice. At present, the conceptual tendency of leader is very close to the erroneous explanation that a leader is one who can capitalize a good number of followers and therefore, is the one who should take the best part in everything related to his area of leadership; from there, he tries to obtain the best resources and benefits at his reach, because that unrealistic vision of believing that everything deserves it does not provide the facilities for solving problems within the scope where he performs his work. For this reason, there is a need to achieve substantial changes, in order to exercise sustainable leadership, which proposes analysis, reflections, examples of centers and experiences as a practical orientation for education professionals.
Keywords: Sustainable leadership; change strategy; education system